If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x (-7)+8-(-10)=0
We simplify the equation to the form, which is simple to understand
8x(-7)+8-(-10)=0
Reorder the terms in parentheses
+(-56x)+8-(-10)=0
Remove unnecessary parentheses
-56x+8-(-10+)=0
Remove unnecessary parentheses
-56x+8+10=0
We move all terms containing x to the left and all other terms to the right.
-56x=0-8-10
We simplify left and right side of the equation.
-56x=-18
We divide both sides of the equation by -56 to get x.
x=0.32142857142857
| 7=-16x^2+24x+1 | | 1.5=10*1 | | 15(-21x+20)=15(-4x+122) | | 2x-3=8x-33 | | 6.2x+6.6-3.4x=20.6 | | 23=3x | | -17=3x-8 | | -5x+46=5+9(8x-4) | | a^3-1698a-2704=0 | | -4x-10=11 | | 1m+10=80 | | 33-x=222 | | 3(9x+7)=27x-1 | | 5(3-2x)=10(4-2x)-85 | | 4(x-10)=5x-45 | | 2x-5x-2=-3+4x-43 | | y=-1+-0.1666666667x | | IV=ir | | a^4-1698a-2704=0 | | 88-6x=-10x+85 | | -46-8x=5(-7x+7) | | 3=5-2 | | 75+10=15h | | 2(1.5)-3y=2 | | 4u-6=-2 | | p-0.30p=25.20 | | -20=4w | | 8x+6x-20=60-6x | | 7x+4q=8+3q | | 2(y)+8=8 | | y=x^3-6x^2-36x+15 | | 8=0.25(-m-1) |